Psychological response to an emergency in virtual reality: Effects of victim ethnicity and emergency type on helping behavior and navigation. (July 2015) - Gamberini, Luciano; Chittaro, Luca; Spagnolli, Anna; Carlesso, Claudio
Highlights: A Black or White virtual human asks participants for help. Two types of simulated emergency are manipulated. Navigation behavior and anxiety change during the simulated emergency. Racial discrimination is observed. Situational aspects of the emergency affect racial discrimination. Abstract: Virtual environments are increasingly used for emergency training, but tend to focus mainly on teaching prescribed emergency procedures. However, social psychology literature highlights several factors that can bias individual response to an emergency in the real world, and would be worth considering in virtual training systems. In this paper, we focus on withdrawal of help due to racial discrimination and explore the potential of virtual environments to trigger this bias in emergency situations. We also test if a virtual emergency is actually reacted to as an emergency. We use an immersive virtual environment (IVE) where a victim issues help requests during two different emergency situations (time pressure or fire). While experiencing the emergency, white participants ( N  = 96) receive a request for help from a black or white virtual human. The results show a psychological response to the virtual experience consistent with an emergency situation (increased state anxiety and increased frequency of collisions with objects in the environment) and biased by racial discrimination in help provision. In addition, racial discrimination increases under time pressure, but not in a fire. The implications for virtual training are discussed.